2021
DOI: 10.3390/polym13081328
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Interfacial Compatibility, Microstructure and Physico-Chemical Properties of Polyimide/Organically Modified Silica Nanocomposite Membrane

Abstract: Polyimide-silica (PI-Silica) composites are of tremendous research interest as high-performance materials because of their excellent thermal and mechanical properties and chemical resistance to organic solvents. Particularly, the sol-gel method of fabricating such composites is popular for manipulating their properties. In this work, PI-silica composite films are synthesized by the sol-gel method and thermal imidization from the solution mixtures of hydrolyzed tetraethoxysilane (TEOS) (or glycidoxypropyltrimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The absorption peak at 1742 cm −1 corresponds to the tensile vibration of the CO bond of the ester group in FPE, and the absorption peak at 1262 cm −1 corresponds to the tensile vibration of the CO bond 27 . The absorption peak at 1095 cm −1 is the antisymmetric tensile vibration of the SiOSi bond 37,38 while the peak pair at 800 cm −1 also corresponds to the vibration of the SiO bond 39,40 . In addition, from 1063 cm −1 to 723 cm −1 , with the increase in the composition of BNNS, it can be observed that the absorption peak gradually widens, which is caused by the stretching vibration of the BN bond.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The absorption peak at 1742 cm −1 corresponds to the tensile vibration of the CO bond of the ester group in FPE, and the absorption peak at 1262 cm −1 corresponds to the tensile vibration of the CO bond 27 . The absorption peak at 1095 cm −1 is the antisymmetric tensile vibration of the SiOSi bond 37,38 while the peak pair at 800 cm −1 also corresponds to the vibration of the SiO bond 39,40 . In addition, from 1063 cm −1 to 723 cm −1 , with the increase in the composition of BNNS, it can be observed that the absorption peak gradually widens, which is caused by the stretching vibration of the BN bond.…”
Section: Resultsmentioning
confidence: 94%
“…27 The absorption peak at 1095 cm À1 is the antisymmetric tensile vibration of the Si O Si bond 37,38 while the peak pair at 800 cm À1 also corresponds to the vibration of the Si O bond. 39,40 In addition, from 1063 cm À1 to 723 cm À1 , with the increase in the composition of BNNS, it can be observed that the absorption peak gradually widens, which is caused by the stretching vibration of the B N bond. This can be good proof that SiO 2 nanoparticles and BNNS combine with the FPE matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers have been widely used in electrical insulation [ 1 , 2 , 3 , 4 ], aerospace [ 5 , 6 , 7 , 8 ], energy storage [ 9 , 10 , 11 ] and other fields on account of their excellent electrical properties [ 12 , 13 , 14 ]. Limited by the low dielectric constant of pristine polymer and the poor corona resistance life, the application of polymers in some insulation or high- k fields is, however, restricted [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fillers and fibers are often added to polymers to improve their properties, either their stiffness and strength but also other properties like thermal stability [ 25 , 26 ]. While the impact of near spherical fillers such as glass beads or powders depends generally only on their content in the polymer, fibers have an anisotropic effect.…”
Section: Introductionmentioning
confidence: 99%